The Effect of Edible Coating Based on Starch of Cassava Pell on The Quality and Shelf Life of Guava fruits at Room Temperature - Azhar Husni; Terip Karo-Karo; Era Yusraini (Universitas Sumatera Utara, 2016)
Guava fruits is one of among fruits that had good market prospect both for local trade and export. However, the commodity has perishable properties thus it needs good post harvest handling that could increase its shelf life. The aim of this research was to find the effect of edible coating based on starch of cassava pell on the quality and shelf life of guava fruits at room temperature. This research consisted of two steps, i.e.: Step I was application of edible coating on guava fruits with storage time as single factor i.e. 0, 2, 4, 6, 8, and 10 days. Step II was testing quality of guava fruits with edible coating treatment at the best shelf life compared with control. Parameters analyzed were weight loss, water content, hardness, level of vitamine C, total acid, total soluble solid, color score value, hedonic value of color, flavor, taste, and texture. The results showed that the application of edible coating on guava fruits during storage time had highly significant effect (P<0,01) on all parameters. The application of edible coating on guava fruits at storage time for 6 days had better quality than control. Keywords: Edible coating, guava fruits, starch of cassava pell